2009
DOI: 10.1055/s-0029-1210259
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Exercise in Type I-Diabetics. I. Different Metabolic Reactions during Heavy Muscular Work in Dependence on Actual Insulin Availability

Abstract: The present study focussed on the impact of heavy muscular work upon metabolic homeostasis in insulin dependent (type I) diabetics in situations involving a certain degree of hyper- and hypoinsulinemia. 20 juvenile type I-diabetics were compared with 6 nondiabetic healthy subjects. The diabetics were studied in states of hypo-(trial A) and hyperinsulinemia (trial B) at the start of the exercise. Differences in insulin availability resulted from the different times that had elapsed from the last insulin injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…In contrast to other studies (Berger et al, 1977;Pruett and Maehhim, 1973;Zander et al, 1983), the present findings only showed insignificant changes in plasma glucose behaviour in diabetics, both during hypo-or hyperinsulinemia. Despite certain degrees of hypo-and hyperinsulinemia moderate muscular exercise provoked no marked changes in blood glucose changes, in contrast to exhausting exercise (Zander et al, 1983).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to other studies (Berger et al, 1977;Pruett and Maehhim, 1973;Zander et al, 1983), the present findings only showed insignificant changes in plasma glucose behaviour in diabetics, both during hypo-or hyperinsulinemia. Despite certain degrees of hypo-and hyperinsulinemia moderate muscular exercise provoked no marked changes in blood glucose changes, in contrast to exhausting exercise (Zander et al, 1983).…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies insulin-dependent diabetics exhibited marked metabolic disorders when performing exhausting muscular exercise (Zander et al, 1983). The present studies were carried out under identical experimental conditions of certain degrees of hypo-or hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Glycaemia during exercise can vary inter-as well as intraindividually given that it depends on various factors such as exercise modality and intensity [101][102][103], nutritional status [104], time of insulin injection [105], or pre-exercise glycaemia level [106]. As expected, aerobic [97,[107][108][109][110][111] and to a less important extent, acute high intensity exercise (HIE) [103,110,[112][113][114][115] results in decreased levels of glucose in the T1D patient, which might cause an episode of hypoglycaemia during or after exercise.…”
Section: Changes In Blood Glucose Levels After a Single Bout Of Exercisementioning
confidence: 99%